Achievement Motivation of Physical Education Teachers - Pavel Smela; Petra Pacesova; Branislav Antala; Iveta Cekanova; Hynek Fucik (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
This paper identifies the differences in achievement motivation of the physical education teachers, divided by gender, and the results are compared with national standards. The research sample was comprised of 52 physical education teachers (male: n=22; 41.59±9.95 years old, female: n=30; 39.33±10.67 years old) from Slovakia. A standardized LMI questionnaire consisting of 170 items was used as the research tool. The Shapiro-Wilk test was used to assess the normality of the data. The Mann-Whitney test was used to evaluate the significance of the differences between individual independent samples. The degree of dependence between two groups was expressed by using the r coefficient. Male physical education teachers have significantly higher (p=0.043) achievement motivation compared to female physical education teachers. A comparison of dimensions of achievement motivation of male physical education teachers showed that they achieved significantly higher scores in the dimensions of persistence, fearlessness, and competitiveness. Comparing them with national standards, the achievement motivation of male teachers of physical education corresponds with the 58th percentile (stanine value 5) and of female teachers of physical education with 46th percentile (stanine value 5). The outcomes of this study characterize PE teachers as an elementary component in the teaching process from the aspect of achievement motivation and its dimensions and also indicate the status of PE teachers in society. This study is designated for PE teachers as well as for the general public striving to improve the quality of the teaching process in sports.